Sequência didática com atividades investigativas para o ensino e a aprendizagem de magnetismo no ensino médio - Sefstroem, Gilsemar (2018)
This work aimed to develop a didactic sequence as a strategy for the teaching and learning process of the electromagnetism content. The work was developed in a state public school in the western part of Paraná and it had as target audience students of a third year high school class. In this context, investigative activities were applied, taking into account that our students are not unique, so one can not have a single way to learn or teach. The theoretical basis of this research is based on a cognitive approach. The purpose of this didactic sequence was to offer tools that help teachers to interpret and better understand what can be done in this field, based on the idea of offering a quality education capable of promoting the learning of our students. In the implementation, some aspects, directly or indirectly, had a positive influence on the success of this work. We can highlight points such as: the great receptivity that the investigative activities had for most of the students, through the interest and participation during the classes, mainly some that never participate. They started questioning, interacting with the group and the teacher during the activities, seeking to expand, report and compare everyday situations with what was seen in the classroom.